Analisis Butir Soal Penilaian Ujian Semester Gasal Mata Pelajaran IPS di MTs Darul Muna Ponorogo - Muharromah, Muhammad Miftah; Humaisi, Syafiq (ASANKA : Journal of Social Science and Education, 2020)
ABSTRACTFinal Semester Assessment requires a quality question item instrument so that it can guarantee the quality of the tests presented to students. To get quality questions, before the questions are used each item needs to be analyzed first. Therefore, it is necessary to analyze the items. The objective to be achieved in the discussion of this thesis is to determine the quality of the items from the Odd Semester Final Assessment in the Social Sciences Subject of MTs Darul Muna Ponorogo. This research is a descriptive quantitative research. In this study, researchers used to measure the quality of the questions by using the validity of the questions, the reliability of the questions, the level of difficulty, the difference power and the distracting function manually by using the Microsoft Excel application. The data collection technique in this study used documentation techniques in the form of questions, question grids, answer keys to questions, and students' answers. Based on the results of the item analysis in terms of validity, reliability, level of difficulty, distinguishing power, and deception function, it can be concluded that the quality of the Odd End Semester Assessment (PAS) items in the Social Sciences subject MTs Darul Muna Ponorogo in the 2019/2020 school year is a problem good enough quality. because those who meet the criteria for good (very good, good, moderate) questions in class VII are 38 out of 50 items (76%), in class VIII there are 44 out of 50 items (88%), class IX totals 35 of 50 items questions (70%) ABSTRAKPenilaian Ujian Akhir membutuhkan instrumen soal yang berkualitas sehingga dapat menjamin kualitas tes yang disajikan kepada siswa. Untuk mendapatkan soal yang berkualitas, sebelum soal digunakan tiap soal perlu dianalisis terlebih dahulu. Oleh karena itu perlu dilakukan analisis terhadap item-item tersebut. Tujuan yang ingin dicapai dalam pembahasan skripsi ini adalah untuk mengetahui kualitas materi dari Penilaian Akhir Semester Ganjil Mata Pelajaran Ilmu Sosial MTs Darul Muna Ponorogo. Penelitian ini merupakan penelitian kuantitatif deskriptif. Dalam penelitian ini peneliti mengukur kualitas soal dengan menggunakan validitas soal, reliabilitas soal, tingkat kesulitan, perbedaan daya dan fungsi distraksi secara manual dengan menggunakan aplikasi Microsoft Excel. Teknik pengumpulan data dalam penelitian ini menggunakan teknik dokumentasi berupa soal, kisi soal, kunci jawaban soal, dan jawaban siswa. Berdasarkan hasil analisis butir soal validitas, reliabilitas, tingkat kesukaran, daya pembeda, dan fungsi penipuan, dapat disimpulkan bahwa kualitas butir soal Penilaian Akhir Semester Ganjil (PAS) mata pelajaran IPS MTs Darul. Muna Ponorogo pada tahun ajaran 2019/2020 merupakan masalah kualitas yang cukup baik. karena yang memenuhi kriteria baik (sangat baik, baik, sedang) soal di kelas VII sebanyak 38 dari 50 item (76%), di kelas VIII ada 44 dari 50 item (88%), kelas IX berjumlah 35 dari 50 item pertanyaan (70%).